O saber ser e o saber fazer na Educação Matemática: análise de egressos de um mestrado profissional em ensino - Canuto, érika Carla Alves (2014)
This work was developed in conjunction with the project of the Centre of Education. As part of this larger project, this investigation aims to study the description and analysis of knowledge mobilized in the strict sense of the graduates of the training program Postgraduate Diploma in Teaching Science and Mathematics from the State University of Paraiba (PPGECM / UEPB) in the years 2010 to 2011 the area of mathematics education. We had specific objectives (1) to characterize the profile of the student graduates, (2) conduct geographical mapping of performance of graduates, (3) assess the academic production of PPGECM from specific descriptors, (4) characterize the teaching knowledge and practice subjects focusing on the guidelines of the Development Plan for Education, (5) identify actions that are being developed by these graduates to improve the quality of basic education schools in which they operate. Thus , this dissertation presents the results of analysis using directed to the Development Plan for Education gaze , which is presented by Decree 6.094/2008 28 guidelines that lead teachers to be partakers and share responsibility for the development of basic education , in a quality perspective toward the integral formation of the student. After collection and analysis it was observed that their research, speeches and actions indicate a concern about the quality of basic education and consequently the development of the student, but was also observed limitations on training in the thematic relationships as inclusive education, democratic management , etc.